Assured automatic dynamic reconfiguration of business processes. Issue 104 (February 2022) - Nahabedian, L.; Braberman, V.; D'Ippolito, N.; Kramer, J.; Uchitel, S.
Abstract: In order to manage evolving organisational practice and maintain compliance with changes in policies and regulations, businesses must be capable of dynamically reconfiguring their business processes. However, such dynamic reconfiguration is a complex, human-intensive and error prone task. Not only must new business process rules be devised but also, crucially, the transition between the old and new rules must be managed. In this paper we present a fully automated technique based on formal specifications and discrete event controller synthesis to produce correct-by-construction reconfiguration strategies. These strategies satisfy user-specified transition requirements, be they domain independent – such as delayed and immediate change – or domain specific. To achieve this, we provide a discrete-event control theoretic approach to operationalise declarative business process specifications, and show how this can be extended to resolve reconfiguration problems. In this way, given the old and the new business process rules described as Dynamic Condition Response Graphs, and given the transition requirements described with linear temporal logic, the technique produces a control strategy that guides the organisation through a business process reconfiguration ensuring that all transition requirements and process rules are satisfied. The technique outputs a reconfiguration DCR whose traces reproduce the controller's reconfiguration strategy. We illustrate and validate the approach using realistic cases and examples from the BPM Academic Initiative. Highlights: Fully automated technique that produces correct-by-construction reconfiguration strategies. Increase the usability of an existing technique by providing a business process notation instead of a transition system. Formalisation of previous work to increase understandability and to provide more guarantees about proposed solution.